Cholemic Nephropathy Reloaded - Fickert, Peter; Rosenkranz, Alexander R. (Seminars in Liver Disease, 2020)
Acute kidney injury (AKI) is a dreaded complication in patients with liver disease and jaundice, since it is associated with significant morbidity and mortality. Cholemic nephropathy (CN) is thought to represent a widely underestimated important cause of AKI in advanced liver diseases with jaundice. The umbrella term CN describes impaired renal function along with histomorphological changes consisting of intratubular cast formation and tubular epithelial cell injury directed primarily toward distal nephron segments. In cholestasis, biliary constituents may be excreted via the kidney and bilirubin or bile acids may trigger tubular injury and cast formation, but as we begin to understand the underlying pathophysiologic mechanisms, we become increasingly aware of the urgent need for clearly defined diagnostic criteria. In the following, we aim to summarize current knowledge of clinical and morphological characteristics of CN, discuss potential pathomechanisms, and raise key questions to stimulate evolution of a research strategy for CN.
Keywords: acute kidney injury; cholestasis; hepatorenal syndrome; advanced liver disease; jaundice